2016
DOI: 10.1159/000445549
|View full text |Cite
|
Sign up to set email alerts
|

Menthol Modulates Pacemaker Potentials through TRPA1 Channels in Cultured Interstitial Cells of Cajal from Murine Small Intestine

Abstract: Background/Aims: ICCs are the pacemaker cells responsible for slow waves in gastrointestinal (GI) smooth muscle, and generate periodic pacemaker potentials in current-clamp mode. Methods: The effects of menthol on the pacemaker potentials of cultured interstitial cells of Cajal (ICCs) from mouse small intestine were studied using the whole cell patch clamp technique. Results: Menthol (1 - 10 μM) was found to induce membrane potential depolarization in a concentration-dependent manner. The effects of various TR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 69 publications
0
23
0
Order By: Relevance
“…Moreover, it has been shown that ICCs undergo apoptosis over time, and that ICC regeneration is required for the maintenance of normal ICC networks in healthy tissues [29]. Furthermore, menthol-induced membrane potential depolarizations, that occur in G-protein, Ca 2+ pathways via TRPA1 M2 and M3 receptors, were shown to be involved in this process [30,31]. Various factors, including regional obstruction and subsequent proximal dilation, and nervous system and immune system injury can lead to ICC damage and loss [26].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been shown that ICCs undergo apoptosis over time, and that ICC regeneration is required for the maintenance of normal ICC networks in healthy tissues [29]. Furthermore, menthol-induced membrane potential depolarizations, that occur in G-protein, Ca 2+ pathways via TRPA1 M2 and M3 receptors, were shown to be involved in this process [30,31]. Various factors, including regional obstruction and subsequent proximal dilation, and nervous system and immune system injury can lead to ICC damage and loss [26].…”
Section: Discussionmentioning
confidence: 99%
“…Interstitial cells of Cajal (ICCs) regulate normal GI function and mediate neuromuscular signaling [32,33]. Therefore, ICCs have an important role in controlling GI motility.…”
Section: Discussionmentioning
confidence: 99%
“…It appears that menthol in the range of submicromolar to low-micromolar concentrations, causes activation of TRPA1 channel, whereas at higher concentrations menthol leads to a reversible blockade of the channel (Karashima et al, 2007). Menthol has also been shown to induce membrane depolarizations by activating TRPA1 channels in interstitial cells of Cajal (Kim et al, 2016). While activation of TRPM8 by menthol occurs with an EC 50 of approximately in the range of 4–80 μM (McKemy et al, 2002; Peier et al, 2002; Behrendt et al, 2004), higher menthol concentrations are required for modulation of other thermosensitive TRP channels.…”
Section: Effects Of Menthol On Ion Channelsmentioning
confidence: 99%